Investigation of temperature dependence of neutron yield and electron screening potential for the d(d, n)3He reaction proceeding in deuterides ZrD2 and TiD2; Physics of Atomic Nuclei; Vol. 75, iss. 8 - Bystritsky V. M.; Bystritskii Vit. M.; Dudkin G. N. Gennadiy Nikolaevich; Filipowicz M.; Gazi S.; Huran J.; Kobzev A. P.; Mesyats G. A. Gennady Andreyevich; Nechaev B. A. Boris Aleksandrovich; Padalko V. N. Vladimir Nikolaevich; Parzhitskii S. S.; Pen’kov F. M.; et al. (2012, 2012)
Title screen